Feedback de AGN em galáxias do Projeto Manga: uma análise da distribuição e cinemática do gás ionizado - Machado, Alice Deconto (2019)
By the end of the XX century, large data surveys began due to the development of powerful telescopes. The Sloan Digital Sky Survey (SDSS) is one of these surveys and comprehend subprojects like the Mapping Nearby Galaxies at Apache Point Observatory (MaNGA). The MaNGA project aims to map 10 thousand nearby galaxies in order to better understand the phenomena behind the formation and evolution of these objects. The project also uses another XXI century innovation: the integral field spectroscopy. This type of spectroscopy, unlike the others, allows the analysis of specific regions of the observed object. One of these regions is the galactic nucleus, which in some galaxies present a huge luminosity that cannot be explained only by considering the stellar continuum. In these cases, the nucleus is said active (AGN: Active Galactic Nuclei) and its high energy emission is attributed to the process of matter accretion through a supermassive black hole located in the center of the galaxy. Depending on the physical and spectral features, an AGN may be classified in different types. The active galaxies observed by the MaNGA project are, mostly, LINER and Seyfert galaxies. The matter accretion process may lead to AGN feedback, such as ionized gas outflows. Feedback is responsible for controlling the growth and evolution of galaxies, interfering in the star formation and in the host galaxy kinematics. These processes can reach kiloparsec scales. In the present work, the kinematics of active and non-active galaxies is analysed in order to detect ionized gas outflows and estimate their power and extensions. A spectral fitting was done using the GANDALF code and kinematics profiles in terms of effective radius were elaborated. The main sample is composed by 170 AGN selected from the MaNGA project and was separated into subsamples based on the galaxies’ luminosity and morphology. A sample of control galaxies was also defined so that the main properties of these objects are similar to that of the AGN. By analysing the global profiles, it can be noticed that, on average, the most luminous AGN present higher residual velocities and velocity dispersions than their respective control galaxies in all the radial bins considered (0.2 ≤ R ≤ 1.0Re). Besides that, the mean outflow extension is smaller than that of the narrow line regions (NLR): outflows presented an extension of around 40% of the effective radius, while the NLR displayed 70%. However, the extensive NLR tend to host the biggest outflows. Regarding ionized gas ejection rates, the values vary between 10−4 and 10−2 M yr−1. Similarly, the kinetic power is low, going from 1035 to 1039 erg s−1. These results suggest that AGN outflows are not powerful enough to affect the kinematics and the evolution of their respective hosts galaxies, in spite of being detect in the sample’s galaxies.